A Study On Perception Of Business Students On The Future Job Market: A Case Study Of Umma University - Farah, Salah Abdirahman; Ali, Hussein Abdi (International Journal of Scientific Research and Management (IJSRM), 2018)
The perception of future country’s labor is important to be studied. The way they perceive the market in general and their future employers in particular cannot be wished away. The world has become very dynamic and so the employers. The needs of the market changes with the influence of so many factors among them the dynamism of technology. Students join courses they perceive important for them in one way or the other. One major factor why the youth pursue courses is to benefit out of it through gainful employment. Employers on the other hand are complaining about universities churning out half-baked graduates that can hardly cope with the stringent needs of the market. That the graduates are not productive and what they have being trained on is not relevant to the needs of specific jobs. This has led to many employers organizing short trainings for their new recruits.In light of the above, the study sought to understand the perception of business students towards the future job market. It found out that close to two-thirds of business students have high expectations in terms of salaries and other benefits. This makes business courses being pursued by many students. Very few of the students have less expectations. More than half of the respondents are for the opinion that they will get a job during their first six months of graduation. High grades, good communication skills and having confidence are the major preferences of employers according to the research. The major causes of unemployment among the youth are lack of creation of job opportunities which has led to tribalism and nepotism in employment. This has locked out many qualified job seekers. Majority of business students prefer searching for a job rather than creating job opportunities themselves. A lot has to be done in order to streamline the courses offered by universities in order to cater for the needs of the market. There should be creation of awareness among the youth so that they prepare themselves for these needs. With these, both the students and their future employers will benefit and hence greater productivity.